Systematic review on human skin-compatible wearable photoplethysmography sensors - Lee, Inho; Park, Nakkyun; Lee, Hanbee; Hwang, Chuljin; Kim, Joo Hee; Park, Sungjun (Applied Sciences (Switzerland), 2021)
The rapid advances in human-friendly and wearable photoplethysmography (PPG) sensors have facilitated the continuous and real-time monitoring of physiological conditions, enabling self-health care without being restricted by location. In this paper, we focus on state-of-the-art skin-compatible PPG sensors and strategies to obtain accurate and stable sensing of biological signals adhered to human skin along with light-absorbing semiconducting materials that are classified as silicone, inorganic, and organic absorbers. The challenges of skin-compatible PPG-based monitoring technologies and their further improvements are also discussed. We expect that such technological developments will accelerate accurate diagnostic evaluation with the aid of the biomedical electronic devices.
Keywords: Health-care platform; Optoelectronic device; Oximeters; Photodiodes; Phototransistors; PPG sensors; Skin electronic